Is the Discretionary Income Effect of Oil Price Shocks a Hoax? - Christiane Baumeister; Lutz Kilian; Xiaoqing Zhou (Center for Economic Studies and ifo Institute (CESifo), 2017)
The transmission of oil price shocks has been a question of central interest in macroeconomics since the 1970s. There has been renewed interest in this question after the large and persistent fall in the real price of oil in 2014-16. In the context of this debate, Ramey (2017) makes the striking claim that the existing literature on the transmission of oil price shocks is fundamentally confused about the question of how to quantify the effect of oil price shocks. In particular, she asserts that the discretionary income effect on private consumption, which plays a central role in contemporary accounts of the transmission of oil price shocks to the U.S. economy, makes no economic sense and has no economic foundation. Ramey suggests that the literature has too often confused the terms-of-trade effect with this discretionary income effect, and she makes the case that the effects of the oil price decline of 2014-16 on private consumption are smaller for a multitude of reasons than suggested by empirical models of the discretionary income effect. We review the main arguments in Ramey (2017) and show that none of her claims hold up to scrutiny.
Keywords: C51; Q43; 330; stimulus; oil price decline; discretionary income effect; expenditure share; gasoline; net oil imports